2012
DOI: 10.1007/s00259-012-2298-2
|View full text |Cite|
|
Sign up to set email alerts
|

PET imaging with a [68Ga]gallium-labelled PSMA ligand for the diagnosis of prostate cancer: biodistribution in humans and first evaluation of tumour lesions

Abstract: The biodistribution of the novel (68)Ga-PSMA tracer and its ability to detect PC lesions was analysed in 37 patients. Within healthy organs, kidneys and salivary glands demonstrated the highest radiotracer uptake. Lesions suspicious for PC presented with excellent contrast as early as 1 h p.i. with high detection rates even at low PSA levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
618
1
25

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 816 publications
(673 citation statements)
references
References 13 publications
29
618
1
25
Order By: Relevance
“…68 Ga-PSMA-HBED-CC has been compared to 11 Cfluoromethylcholine in the diagnosis of PC and has been found to be more sensitive in the diagnosis of lymph node, central bone, and liver metastases [9]. Biodistribution studies have revealed uptake of the radiotracer in the lacrimal glands, salivary glands, liver, spleen, kidneys, small and large bowel besides lesions suspicious for PC [10]. Atypical uptake of this tracer has been reported in the celiac ganglion mimicking lymph nodes [11].…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-PSMA-HBED-CC has been compared to 11 Cfluoromethylcholine in the diagnosis of PC and has been found to be more sensitive in the diagnosis of lymph node, central bone, and liver metastases [9]. Biodistribution studies have revealed uptake of the radiotracer in the lacrimal glands, salivary glands, liver, spleen, kidneys, small and large bowel besides lesions suspicious for PC [10]. Atypical uptake of this tracer has been reported in the celiac ganglion mimicking lymph nodes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, both 18 68 Ga-PSMA have been studied in humans, and both reportedly were capable of detecting sites of metastatic prostate cancer. 125,126 In a subsequent, small clinical trial, 68 Ga-PSMA detected more lesions than 18 F-choline. 127 Somatostatin receptors are overexpressed on neuroendocrine tumor cells.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 94%
“…While further studies are required to assess the efficacy of anti-3-18 F-FACBC in a larger series of prostate cancer patients, preliminary data reported by Nanni et al in this issue indicate a superiority of anti-3-18 F-FACBC over choline PET/CT in the detection of prostate cancer recurrence [9]. Although not covered in this issue, other novel investigational radiotracers such as radiolabelled prostate-specific membrane antigen [10] and bombesin analogues [11], may also have potential for clinical applications in prostate cancer.…”
Section: Other Pet Tracersmentioning
confidence: 95%